Pengaruh Motivasi Terhadap Kedisiplinan Mahasiswa Kewirausahaan Universitas Negeri Medan - Fadillah Fasha; Esterlia Ginting; Murtini Girsang; Jabal Ahsan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The main pillar in building quality individuals is education. In pursuing education, people today will go to school, where at each level there are rules that must be followed and prohibitions that must be avoided by students. This is useful for building discipline and a sense of responsibility. Motivation can be said to be a tool that can move and encourage people because it can trigger a feeling of enthusiasm and can also change individual behavior to a better place. This research aims to determine the influence of motivation on the discipline of Stambuk Entrepreneurship Students 2023, Medan State University. This research is quantitative research using the ex-post facto method. In analyzing the data that has been collected, this research uses manual calculations with Quantitative Descriptive Statistical Analysis techniques. Based on the results of the analysis, it was found that there was an influence of motivation on the discipline of the 2023 UNIMED Entrepreneurship students with X and Y correlation results of 0.58 or 58%, while the remainder, namely 0.42 (42%) was determined by other variables.